Effect of Addition of Thyroxine in the Treatment of Graves’ Disease: A Systematic Review - Li, Jun; Bai, Litao; Wei, Fan; Wei, Maoying; Xiao, Yao; Yan, Weitian; Wei, Junping (Frontiers in Endocrinology, 2021)
Graves’ disease is the most common cause of hyperthyroidism. Antithyroid drugs, radioiodine ablation, and surgery are the main treatments. Research has demonstrated that adding thyroxine to antithyroid therapy can improve the remission rate, and many similar studies have been conducted subsequently. The purpose of this systematic review was to investigate whether adding thyroxine to various treatments for Graves’ disease has a clinical benefit in remission/relapse rate, stable thyroid function, occurrence of Graves’ ophthalmopathy, etc. A total of 27 studies were included, and the risk of research bias was moderate to high. We discuss the role of thyroxine both in pharmacological and non-pharmacological therapeutic regimens. Overall, the available evidence does not support the indiscriminate addition of thyroxine to various treatments for Graves’ disease, especially in combination with oral antithyroid drugs. Further clinical studies are required to explore the indications of thyroxine addition in the treatment of Graves’ disease.